2018
DOI: 10.3390/s18113798
|View full text |Cite
|
Sign up to set email alerts
|

Indoor Air Quality Real-Time Monitoring in Airport Terminal Areas: An Opportunity for Sustainable Management of Micro-Climatic Parameters

Abstract: Indoor air quality (IAQ) management in public spaces is assuming a remarkable importance. Busy environments, like airport terminals, are currently regarded as possible hotspots and IAQ is a crucial element for passengers and staff protection, as well as a key aspect of airport passenger experience. A one-month monitoring period has been performed on IAQ in the airport of Bologna (Italy), as prototypal example of large regional airport. Four strategic areas within the airport have been equipped with electronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…Manigrasso et al revised all of the possible sources and investigated the ultrafine particle emissions and relative doses deposited in the human respiratory tract [64][65][66]. The importance of the micro-climatic parameters was discussed by Zanni et al, which monitored the IAQ in the airport of Bologna (Italy) as a prototypal example of a large regional airport [67]. Siani et al applied the cluster analysis on a long time series of temperature and relative humidity measurements for identifying the thermo-hygrometric features in a museum [68].…”
Section: Rapp Istisanmentioning
confidence: 99%
“…Manigrasso et al revised all of the possible sources and investigated the ultrafine particle emissions and relative doses deposited in the human respiratory tract [64][65][66]. The importance of the micro-climatic parameters was discussed by Zanni et al, which monitored the IAQ in the airport of Bologna (Italy) as a prototypal example of a large regional airport [67]. Siani et al applied the cluster analysis on a long time series of temperature and relative humidity measurements for identifying the thermo-hygrometric features in a museum [68].…”
Section: Rapp Istisanmentioning
confidence: 99%
“…It is equally important to understand the air quality inside the terminal building as opposed to other parts of the airport. Two recent studies by Zanni et al [20] and Ren et al [21] have examined the FP concentrations in airport terminal buildings in Italy and China, respectively. Other air quality parameters measured in the studies include TVOC [20] and UFP [21].…”
Section: Introductionmentioning
confidence: 99%
“…Two recent studies by Zanni et al [20] and Ren et al [21] have examined the FP concentrations in airport terminal buildings in Italy and China, respectively. Other air quality parameters measured in the studies include TVOC [20] and UFP [21]. Whereas Zanni et al concluded that the building's ventilation system appeared to be efficient in terms of filtration [20], Ren et al demonstrated that the building failed to provide sufficient protection for passengers from PM 2.5 and UFP exposures [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The advancement of low-cost IoT sensors, in recent years, has enabled the use of wireless communications and computing for interacting with the physical world. These sensors can measure indoor environmental parameters including IAQ, comfort, lighting, and acoustic conditions [39][40][41]. Many of these low-cost ambient sensors allow portable deployment and different sensors can be easily packed in one board to fit the requirements of different application scenarios.…”
mentioning
confidence: 99%